The effect of methanol production and application in internal combustion engines on emissions in the context of carbon neutrality: A review - Tian, Zhi; Wang, Yang; Zhen, Xudong; Liu, Zengbin (Fuel (Guildford), 2022)
•A detailed review of methanol production and its impact on engine emissions in the context of carbon neutrality.•The method and feasibility of CO2 hydrogenation to methanol are compared and analyzed.•The feasibility of methanol for vehicles is analyzed from different aspects.•Methanol used in SI and CI engines can reduce CO, NOx, soot and PM emissions.•Combining WHR technology further enhances the advantages of methanol used in engines. Methanol is a recognized renewable clean energy. In the context of carbon neutrality, it is of great significance to achieve low-carbon production of methanol fuel and its application in internal combustion (IC) engines to reduce emissions. First, this article systematically introduced and evaluated the technical routes and methods of methanol production from carbon dioxide (CO2) and hydrogen (H2). Then it evaluates the feasibility analysis of the application of methanol in IC engines from different aspects, and the impact of the combustion of methanol fuel in IC engines on emissions. Finally, the research direction of methanol fuel in the future is pointed out.